Peribahasa Melayu penelitian makna & nilai - Zaitul Azma Zainon Hamzah (Penerbit Universiti Putra Malaysia, 2011)
This book systematically organises. 5,737 proverbs making it the most comprehensive and systematic publication of Malay proverbs to.